Google Classroom as Online Media in English Teaching and Learning - Herawati Herawati (Journal of English Education and Teaching, 2022)
Nowadays, the learners are interested in finding way to learn English easily. They are able to have home resources such as technological tools at home and opportunities to use it in their learning process. Google Classroom is a part of the online Google Apps for Education suite of productivity applications for teachers and students in online learning. This study aimed to find out the effectiveness of Google Classroom in enhancing students’ English. The design of this study is a quasi-experimental design (Non design) by one group pre-test and post test design. The population of this study was all of the first semester students of Universitas Musi Rawas. The sample was Karyawan Class students of the first semester of Universitas Musi Rawas. The total of students was as many as 50 students of Karyawan Class. The research sample was selected based on purposive sampling technique. The instruments used in this study were observation and test. The result of this study shows that the significance level smaller than significance (0.05) which indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It means that Using Google Classroom influences teaching learning process positively.